Program pembuatan SOP bidang keuangan untuk meningkatkan kinerja pada UKM Kayu Manis Batam - Wisnu Yuwono; Nimatul Mamuriyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Program of community service aims to improve the capabilities of Kayu Manis Batam SMEs in managing financial management through the making of SOPs conducted in April-August 2019. Methods in this activity include observation, FGD, program design and trial & error, and implementation. The results of the program activities have resulted in five SOPs in the financial sector that have been well implemented by SMEs.